2020
DOI: 10.3390/sym12010164
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Integrated Subjective-Objective MCDM Model for Alternative Ranking in Order to Achieve Business Excellence and Sustainability

Abstract: Achieving sustainability in constant development in every area in today’s modern business has become a challenge on the one hand, and an imperative on the other. If the aspect of business excellence achievement is also added to it, the complexity of the system increases significantly, and it is necessary to model a system considering several parameters and satisfying the multi-criteria function. This paper develops a novel integrated model that involves the application of a subjective-objective model in order … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 35 publications
1
23
0
1
Order By: Relevance
“…The consistency ratios for all four variables’ set are less than 0.1, hence shows acceptable consistency in the judgments of decision makers, Table 8 . The hierarchical structure proposed in Fig 2 is not homogenous such that the number of sub-criteria at second level is not same under each dimensions and will lead to unfair global weights [ 98 ]. Therefore, the CSFs, SM and PVMO in PDE dimension, having the lowest weights of 0.0689 and 0.1171 have been dropped and the sum of their weights have been distributed equally to other three CSFs namely SLM, CD and CQI, Table 9 .…”
Section: Application Of Fuzzy Ahp and Fucommentioning
confidence: 99%
“…The consistency ratios for all four variables’ set are less than 0.1, hence shows acceptable consistency in the judgments of decision makers, Table 8 . The hierarchical structure proposed in Fig 2 is not homogenous such that the number of sub-criteria at second level is not same under each dimensions and will lead to unfair global weights [ 98 ]. Therefore, the CSFs, SM and PVMO in PDE dimension, having the lowest weights of 0.0689 and 0.1171 have been dropped and the sum of their weights have been distributed equally to other three CSFs namely SLM, CD and CQI, Table 9 .…”
Section: Application Of Fuzzy Ahp and Fucommentioning
confidence: 99%
“…This method was integrated into Strengths, Weaknesses, Opportunities, and Threats (SWOT) analysis to obtain values of each SWOT dimension. Marković et al [40] showed that fuzzy PIPRECIA as a subjective Multi-Criteria Decision-Making (MCDM) method can be very successfully applied in integration with other objective methods, such as Criteria Importance Through Intercriteria Correlation (CRITIC). They used an integrated model for the ranking banks in order to achieve business excellence and sustainability.…”
Section: Fuzzy Pivot Pairwise Relative Criteria Importance Assessmentmentioning
confidence: 99%
“…SBE represents a concept with many influencing factors: participation, motivation, professional staff training, a focus on customers, strategic planning, a focus on innovation and continuous improvement, leadership, process management, and most crucially sustainable resource management [16]. As a result, SBE was the target of many researchers and professional organisations through many models, techniques and tools [17][18][19].…”
Section: Introductionmentioning
confidence: 99%